PEMBERDAYAAN EKONOMI PENGUSAHA TAHU ( Studi Tentang Pemberdayaan Pengusaha Tahu melalui Peran Dinas Koperasi, Industri dan Perdagangan Kabupaten Kediri). - Muhamad Bagus Ferdiansyah (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2015)
abstract: ECONOMIC EMPOWERMENT OF ENTREPRENEURS TOFU (Studies Empowering Entrepreneurs Tofu through the role of the Department of Cooperatives, Industry and Trade Kediri District). Empowerment of Cooperatives, Industry and Trade of the Tofu Businessmen. Is a cold process kindness achieved by the government and the private sector need to be empowered in order to achieve an independent local community welfare. Department of Cooperatives, Industry and Trade, empowering entrepreneurs tofu the ways in accordance with the decree, that in the study, there are three main points in the empowerment implemented by Cooperative Agency, industry and trade, that empowerment in the areas of capital, which the Department of Cooperatives, industry, trade and often provide grants that are usually replaced immediately in the form of items required, coaching or giving knowledge to entrepreneurs to learn more about the types of business, and administrators who monitor the Tofu Businessmen that once there is a connection with the Department of Cooperatives, industry and trade as Tofu Businessmen who never get a grant. So expect from the district administration, there is a good relationship between the private sector that Tofu Businessmen the government agencies that the Department of Cooperatives, industry and trade. Constraints and Implementation Support Empowerment Cooperative Agency, industry and trade to entrepreneurs know. Constraints in the implementation of the empowerment arises because, lazily most entrepreneurs know in following training activities and associations of Micro Small and Medium Enterprises District, Kediri. So that products and marketing for entrepreneurs who are inactive to grow. Supporting factors that I know in the field is the board's role PMKM at the Department of Cooperatives, Industry and Commerce which supports the welfare of Tofu Businessmen. Apparatus existing Resources. Further supporting factor in achieving the welfare of the Tofu Businessmen, tofu Culinary Kediri is well-known, so that adds to the interest of marketing. Just how entrepreneurs know how to package products that many consumers demand widely. Keywords: Economic Empowerment, Entrepreneur Tofu Abstrak: PEMBERDAYAAN EKONOMI PENGUSAHA TAHU (Studi Tentang Pemberdayaan Pengusaha Tahu melalui Peran Dinas Koperasi, Industri dan Perdagangan Kabupaten Kediri). Pemberdayaan yang dilakukan Dinas Koperasi, Industri dan Perdagangan terhadap pengusaha tahu. Merupakan proses kebaikan yang dingin dicapai oleh pihak pemerintah dan swasta yang perlu diberdayakan agar mencapai kesejateraan masyarakat daerah yang mandiri. Dinas Koperasi, Industri dan Perdagangan, memberdayakan pengusaha tahu dengan cara-cara sesuai dengan Peraturan Bupati, yakni dalam kajian tersebut terdapat tiga poin utama didalam pemberdayaan yang dilaksanakan oleh Dinas Koperasi, industri dan perdagangan, yakni pemberdayaan dalam bidang Permodalan, dimana pihak Dinas Koperasi, Industi dan perdagangan sering memberikan dana hibah yang biasanya diganti langsung berupa barang yang dibutuhkan, Pembinaan atau memberikan pengetahuan kepada pengusaha untuk lebih mengenal jenis-jenis usahanya, serta pengurus yang memantau usaha tahu yang pernah ada hubungan dengan pihak Dinas Koperasi, industri dan perdagangan misalnya pengusaha tahu yang pernah mendapatkan dana hibah. Sehingga diharapkan dari pemerintah kabupaten, ada hubungan baik antara pihak swasta yakni pengusaha tahu dengan pihak pemerintahan yakni Dinas Koperasi, industri dan perdagangan. Kendala dan Pendukung Penyelenggaraan Pemberdayaan Dinas Koperasi, industri dan perdagangan terhadap pengusaha tahu. Kendala dalam penyelenggaraan pemberdayaan muncul karena, malasnya sebagian besar pengusaha tahu dalam mengikuti kegiatan pelatihan dan perkumpulan Usaha Kecil Menengah Mikro Kab, Kediri. Sehingga produk dan pemasaran bagi pengusaha yang tidak aktif sulit berkembang. Faktor pendukung yang penulis ketahui di lapangan adalah Peran pengurus PMKM pada Dinas Koperasi, Industri dan Perdagangan yang mendukung kesejahteraan pengusaha tahu. Sumber Daya Aparatur yang ada. Faktor pendukung selanjutnya didalam mencapai kesejahteraan para pengusaha tahu adalah Kuliner tahu Kediri yang sudah terkenal, sehingga menambah minat pemasaran. Tinggal bagaimana cara pengusaha tahu mengemas produk agar banyak diminati konsumen secara luas. Â Â Kata Kunci: Pemberdayaan Ekonomi, Pengusaha Tahu